(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Standardization of Ayurvedic formulations is an important step for the establishment of a consistent biological activity, chemical profile, or simply a quality assurance program for production and manufacturing of herbal drugs. WHO specifies guidelines for the assessment of the safety, efficacy and quality of herbal medicines as a prerequisite for global harmonization. Hence it is very essential to ensure that each packet sold in the market is standardized. In this research work, a polyherbal formulation (PHF), Caspa Drops has been taken to establish its standardization level using various physico-chemical parameters. For raw material various parameters such as pH, Moisture content, ash values, HPTLC fingerprinting, assays of marker compounds etc. were carried out to confirm their quality and potency. The presence of the raw materials in the finished product was carried out with the aid of sophisticated instruments. Study results revealed that product was well standardized at selected analytical parameters. All the tests were carried out in triplicates after which their SD was calculated. All the raw materials as well as finished product were found free from heavy metal and microbial contaminants.